Please assist me! I will give the brainliest answer! Plus extra points!!


Consider the following pair of equations:

y = x + 4
y = −2x − 2

Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form.

Respuesta :

Seprum
Step 1: Replace [tex]y[/tex] in the second equation with the right side of first equation like that:
[tex]x+4=-2x-2[/tex]

Step 2: Solve that simple equation:
[tex]x+4=-2x-2[/tex]
[tex]x+2x=-2-4[/tex]
[tex]3x=-6[/tex]
[tex]x=-6/3=-2[/tex]

Step 3: Replace [tex]x[/tex] of first equation with found value and solve it:
[tex]y=-2+4[/tex]
[tex]y=2[/tex]

So, the solution is: [tex]x=-2[/tex] and [tex]y=2[/tex].
ACCESS MORE